Combining a nine‐crystal multi‐analyser stage with a two‐dimensional detector for high‐resolution powder X‐ray diffraction. Issue 6 (28th November 2018) - Dejoie, Catherine; Coduri, Mauro; Petitdemange, Sébastien; Giacobbe, Carlotta; Covacci, Ezio; Grimaldi, Olivier; Autran, Pierre-Olivier; Mogodi, Mashikoane Wilson; Šišak Jung, Dubravka; Fitch, Andrew N.
Abstract : The high‐resolution powder diffraction setup of the ESRF ID22 beamline has been combined with a two‐dimensional Pilatus3 X CdTe 300 K‐W detector, offering new possibilities in terms of data handling and improving the overall performance of high‐resolution powder diffraction. Abstract : The high‐resolution powder diffraction beamline at ESRF (ID22), built with a dual‐undulator source on the 6 GeV storage ring, combines a wide continuous range of incident energy (6–80 keV) with high brightness, offering the possibility to carry out high‐flux high‐resolution powder diffraction measurements. In routine operation, a bank of nine scintillation detectors is scanned vertically to measure the diffracted intensity versus 2gθ, each detector being preceded by an Si 111 analyser crystal. Although the current detector system has operated successfully for the past 20 years, recent developments in detector technology could be exploited to improve the overall performance. With this in mind, as a test, a two‐dimensional Pilatus3 X CdTe 300 K‐W pixel detector has been mounted on the arm of the diffractometer, replacing the nine scintillator detectors. At each nominal 2gθ value, a two‐dimensional image is recorded showing nine distinct regions corresponding to the diffraction signals passing via each of the analyser crystals. This arrangement offers new flexibility in terms of data handling and processing, with the possibility to optimize both peak shape and statistics, to remove parasitic effects, and to gain spatial resolution information. Combining the high efficiency of a hybrid photon‐counting area detector with the high angular resolution given by analyser crystals is an effective approach to improving the overall performance of high‐resolution powder diffraction.